Propagating speedups during quiescence escalate to the 2020–2021 surge of Sít’ Kusá, southeast Alaska - Jukes Liu; Ellyn M. Enderlin; Timothy C. Bartholomaus; Yoram Terleth; Thomas Dylan Mikesell; Flavien Beaud (Journal of Glaciology)
We use satellite image processing techniques to measure surface elevation and velocity changes on a temperate surging glacier, Sít’ Kusá, throughout its entire 2013–2021 surge cycle. We present detailed records of its dynamic changes during quiescence (2013–2019) and its surge progression (2020–2021). Throughout quiescence, we observe order-of-magnitude speedups that propagate down-glacier seasonally from the glacier's upper northern tributary, above a steep icefall, into the reservoir zone for the surging portion of the glacier. The speedups initiate in fall and gradually accelerate through winter until they peak in late spring, ~1 − 2 months after the onset of melt. Propagation distance of the speedups controls the distribution of mass accumulation in the reservoir zone prior to the surge. Furthermore, the intensity and propagation distance of each year's speedup is correlated with the positive degree day sum from the preceding melt season, suggesting that winter melt storage drives the seasonal speedups. We demonstrate that the speedups are kinematically similar to the 2020–2021 surge, differing mainly in that the surge propagates past the dynamic balance line at the lower limit of the reservoir zone, likely triggered by the exceedance of a tipping point in mass accumulation and basal enthalpy in the reservoir zone.